1980
DOI: 10.1002/jbm.820140406
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of plasma proteins with polymers. I. Relationship between polymer surface energy and protein adsorption/desorption

Abstract: Adsorption of bovine albumin, gamma-globulin and fibrinogen from phosphate buffer solution (pH = 7.5) onto several polymer films was studied using the radioiodinated proteins (125I). The kinetics of desorption of the proteinated polymer films in bovine plasma was determined. Contact angle measurements on these same polymers allowed the calculation of dispersive (WA d) and polar (Ip) components of the polymer-protein solution system. Results from these measurements show that the nondispersive-dispersive force b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(79 citation statements)
references
References 12 publications
9
70
0
Order By: Relevance
“…The adsorption amounts expected for the two modes have already been estimated to be 0.9 and 0.25 mg cm À2 for HSA, and 1.7 and 0.18 mg cm À2 for fibrinogen, respectively. 15 The present data ranged between these values, except for the adsorption amount of HSA onto the st-PMMA film, indicating monolayer coverage for the proteins adsorbed. Interestingly, a greater amount of HSA and fibrinogen with the end-on mode was adsorbed onto the stereocomplex film as compared to the other homogeneous films.…”
Section: Resultssupporting
confidence: 46%
“…The adsorption amounts expected for the two modes have already been estimated to be 0.9 and 0.25 mg cm À2 for HSA, and 1.7 and 0.18 mg cm À2 for fibrinogen, respectively. 15 The present data ranged between these values, except for the adsorption amount of HSA onto the st-PMMA film, indicating monolayer coverage for the proteins adsorbed. Interestingly, a greater amount of HSA and fibrinogen with the end-on mode was adsorbed onto the stereocomplex film as compared to the other homogeneous films.…”
Section: Resultssupporting
confidence: 46%
“…Calculated af488-HSA coverage densities at 90 min of adsorption agree well with data published in the literature [17,32,35]. af488-HSA adsorption on the control OTS surfaces (i.e., on uniformly annealed and non-annealed OTS films on glass) were similar to those for the respective stamped areas of the OTS patterned surfaces, while the adsorbed amount of af488-HSA on the clean glass surface reached an average density of only 0.057 μg/cm 2 after 90 min of adsorption.…”
Section: Albumin Adsorptionsupporting
confidence: 86%
“…It was reported that theoretical amounts of BSA and BPF adsorbed on the surface in a monolayered state are 0.9 g/cm 2 and 1.7 g/cm 2 , respectively. 32 On the surface of PMB30, the amount of adsorbed proteins was less than these theoretical values. Thus it is possible that the phosphorylcholine group can reduce protein adsorption effectively.…”
Section: Discussionmentioning
confidence: 77%